Autopsy: The Changing Trends .......... IJMTFM (2011) 1(1): 17-23 - Kumar Mohanty, Manoj; Singh, Bhoopendra; M, Arun; G. Menezes, Ritesh; Palimar, Vikram (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Investigative dissection of a dead body primarily to find out cause of death is known as postmortem examination or Necropsy. Medicolegal autopsy or Forensic autopsy is performed following instructions of legal authority in sudden, suspicious, obscure, unnatural or criminal deaths. Autopsies are of two types i.e. Medico legal autopsy and Pathological or Hospital autopsy. Traditional procedures of autopsy need extensive dissection, which lead to mutilation of the dead body. As such, it has been unpopular amongst various religions and communities. To overcome this, many other variants of autopsies have developed over the years. Though many consider the autopsy to be an antiquated procedure, many changes have already occurred in the procedure. This paper attempts to explain various types of autopsies, the changing trends and analyses the advantages and disadvantages associated with them.